Characterization of the Proximal Long Head of Biceps Tendon Anatomy Using Magnetic Resonance Imaging: Implications for Biceps Tenodesis. Issue 2 (February 2021) - Ek, Eugene T.; Philpott, Andrew J.; Flynn, Jennifer N.; Richards, Nada; Hardidge, Andrew J.; Rotstein, Andrew H.; Wood, Ayla D.
Background: Biceps tenodesis is a common treatment for proximal long head of biceps (LHB) tendon pathology. To maintain biceps strength and contour and minimize cramping, restoration of muscle-length tension and appropriate positioning of the tenodesis is key. Little is known about the biceps musculotendinous junction (MTJ) anatomy, especially in relation to the overlying pectoralis major tendon (PMT), which is a commonly used landmark for tenodesis positioning. Purpose: To characterize the in vivo topographic anatomy of the LHB tendon, in particular the MTJ relative to the PMT, using a novel axial proton-density magnetic resonance imaging (MRI) sequence. Study Design: Descriptive laboratory study. Methods: In total, 45 patients having a shoulder MRI for symptoms unrelated to their biceps tendon or rotator cuff were prospectively recruited. There were 33 men and 12 women, with a mean age of 37 ± 13 years (range, 18-59 years). All patients underwent routine shoulder MRI scans with an additional axial proton density sequence examining the LHB tendon and its MTJ. Three independent observers reviewed each MRI scan, and measurements were obtained for (1) MTJ length, (2) the distance between the proximal MTJ and the superior border of the PMT (MTJ-S), (3) the distance between the distal MTJ to the inferior border of the PMT, and (4) the width of the PMT. Results: The average position of the MTJ-S was 5.9 ± 10.8 mm distal to the superior border of the PMT. The mean MTJ length was 32.5 ± 8.3 mm and the width of the PMT was 28.0 ± 7.3 mm. We found no significant correlation between patient age, height, sex, or body mass index and any of the biceps measurements. We observed wide variability of the MTJ-S position and identified 3 distinct types of biceps MTJ: type 1, MTJ-S above the PMT; type 2, MTJ-S between 0 and 10 mm below the superior border of the PMT; and type 3, MTJ-S >10 mm distal to the superior PMT. Conclusion: In this study, the in vivo anatomy of the LHB tendon is characterized relative to the PMT using a novel MRI sequence. The results demonstrate wide variability in the position of the MTJ relative to the PMT, which can be classified into 3 distinct subtypes or zones relative to the superior border of the PMT. Understanding this potentially allows for accurate and anatomic placement of the biceps tendon for tenodesis. Clinical Relevance: To our knowledge, this is the first study to radiologically analyze the in vivo topographic anatomy of the LHB tendon and its MTJ. The results of this study provide more detailed understanding of the variability of the biceps MTJ, thus allowing for more accurate placement of the biceps tendon during tenodesis.